Migrant Radicalism and Activism in Australia: The Transnational Experience of Pierina Pirisi. Issue 2 (3rd April 2019) - Battiston, Simone
ABSTRACT: This article examines the transnational experience of Italian-born Pietrina ("Pierina") Pirisi, who took an active part in the communist and ethnic rights movements in Australia from 1972 until her return to Italy in 1984. For Pierina, the paths of migration, radicalism and activism intertwined when she moved from her native Sardinia to Sydney and joined the Communist Party of Australia, the Italian Communist Party in Australia, and the Italian Federation of Migrant Workers and their Families. Before emigrating, Pierina had begun developing a radical political awareness, which migration only strengthened. Through Pierina's story, this article expands our understanding and traces the evolution of the involvement in far-left politics and community-based initiatives of newcomers from Italy who had experienced, or had been inspired by, the movements of "1968". By shuttling between Australia and Italy's communist experiences, Pierina's story complicates our understanding of migrant activism, yet it enriches our knowledge by adding transnational, pre- and post-emigration elements to the history of the politicisation of migrants. This article demonstrates the value of a multifaceted approach to historical analysis and interpretation, and the engagement of multiple sources, from immigration and security files to oral history, when examining post-1968 political activism by and for migrants.